2013
DOI: 10.1682/jrrd.2013.02.0042
|View full text |Cite
|
Sign up to set email alerts
|

Objective and subjective measures reflect different aspects of balance in multiple sclerosis

Abstract: Abstract-The objective of this study was to evaluate relationships between subjective and objective measures of balance in multiple sclerosis (MS). In 54 subjects with MS, balance was measured objectively with the Sensory Organization Test (SOT) using dynamic posturography and subjectively with the Activitiesspecific Balance Confidence (ABC) Scale and the Falls Efficacy Scale-International (FES-I). MS-related disability was assessed with the Expanded Disability Status Scale (EDSS). Relationships between the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…Balance f CSI is a complex physiological process that many clinical measures of postural control are unable to quantify. The computerized dynamic posturography sensory organization test (CDP-SOT) has initial support as a valid measure of balance f CSI and falls in people with MS. 7,8 It has been applied as a primary outcome in controlled trials of balance 9 and vestibular rehabilitation 10 training for individuals with MS, supporting the responsiveness of the CDP-SOT to targeted treatment of impaired balance f CSI in this patient population. The CDP-SOT has also been applied as a gold standard for the validation of novel outcome measures of postural control.…”
Section: Computerized Dynamic Posturographymentioning
confidence: 89%
“…Balance f CSI is a complex physiological process that many clinical measures of postural control are unable to quantify. The computerized dynamic posturography sensory organization test (CDP-SOT) has initial support as a valid measure of balance f CSI and falls in people with MS. 7,8 It has been applied as a primary outcome in controlled trials of balance 9 and vestibular rehabilitation 10 training for individuals with MS, supporting the responsiveness of the CDP-SOT to targeted treatment of impaired balance f CSI in this patient population. The CDP-SOT has also been applied as a gold standard for the validation of novel outcome measures of postural control.…”
Section: Computerized Dynamic Posturographymentioning
confidence: 89%
“…[1,29] Considering the fact that even people with MCI or SCI have impaired balance [6,7,30] and various parameters of balance control were associated with the severity of cognitive dysfunction, [3,6,7] assessment of postural instability in AD might provide a clue for an earlier diagnosis of AD and a method to provide further individualized management. However, many of these studies [5,810] used self-reported questionnaires for falling or simple tests of walking abilities for given time, which provided limited information about participant performances. Thus, we adopted CDP for quantitative assessment of balance control in AD and hypothesized that CDP performance might be more impaired in AD than in controls as in the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The assessments of posture in most previous studies [5,810] were subjective and non-quantitative, as they were based on self-reported questionnaires or simple neurological examinations. It is generally accepted that computerized dynamic posturography (CDP) has the ability to evaluate balance quantitatively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed similar results when comparing center of pressure measures using a force platform with clinical-based measures such as the SPPB [36,37]. However, the moderate correlation indicates that different aspects of balance are being measured by the accelerometer- specific Balance Confidence (ABC) scale, which was highly correlated with the GES, showed a similar correlation between postural sway and the ABC scale [38].…”
Section: Discussionmentioning
confidence: 73%